Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Online: (Studi Kasus Pada Mahasiswa Perbankan Syariah STAIN Mandailing Natal) - Alfian, Ian (Program Studi Manajemen Bisnis Syariah STAIN Mandailing Natal, 2020)
This study aims to determine how the influence of variables, risks and promotions on purchasing decisions at potential universities is case study programs in sharia banking students. The method used in this study uses quantitative research with multiple regression analysis using the help of SPSS program version 17. The results of the study are the first online consumer purchasing decisions with promotions that contribute 24.9%, both variables with benefits of 23.6% and all three variables with a risk of 23%. The results of the significance test partially indicate the existence of variables, risks, and promotions for online purchasing decisions significantly.